What is the difference between the two lateral x-rays taken during left s1 transforaminal epidural steroid injection? (Bilimsel Mektup) - (:unkn) unknown (My University, 2014)
0
Sol S1 transforaminal epidural steroid enjeksiyonu sırasında çekilen iki lateral graf arasındaki fark nedir? (Scientifc Letter)
Keywords: Rehabilitasyon